Pemanfaatan Citrus hystrix DC oleh Pedagang Tumbuhan Obat di Pasar Tradisional Kabanjahe Kabupaten Karo - Marina Silalahi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Citrus hystrix or Jeruk Purut is a type of Rutaceae family that is used as food and traditional medicinal ingredients. Various traditional dishes in Indonesia use Citrus hystrix as a cooking spice and are believed to give a distinctive and refreshing aroma. The use of plants as cooking spices or medicines is related to their bioactive compounds, especially in their use as medicine. The purpose of this study was to explain the relationship between the use of Citrus hystrix and its bioactivity. This study combines market surveys in several traditional markets in North Sumatra and literature studies on the results of research published online and offline about the bioactivity of Citrus hystrix. Respondents in this study were all medicinal plant traders who trade Citrus hystrix. Some of the keywords used for online searches are Citrus hystrix and bioactivity of Citrus hystrix, then they are synthesized so they can explain the purpose. Citrus hystrix has long been traded in the traditional markets of Kabanjahe, Berastagi, and Pancur Batu under the local name